A STEM-BASED INTERACTIVE E-MODULE FOR STRENGTHENING STATISTICAL LITERACY IN MATHEMATICS LEARNING: DEVELOPMENT AND EVALUATION STUDY - Bintari Solafide Pasaribu; Abdul Hamid K; R. Mursid (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aimed to develop and evaluate a STEM-based interactive e-module to strengthen students’ statistical literacy in mathematics learning. The study employed a Research and Development (R&D) approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The research was conducted at SMP Negeri 3 Medan involving 64 Grade VIII students, with 32 students in the experimental class and 32 students in the control class. The developed e-module integrated Science, Technology, Engineering, and Mathematics (STEM) principles with interactive multimedia features, including animations, videos, simulations, and contextual statistical problem-solving activities. The quality of the e-module was assessed through validity, practicality, and effectiveness evaluations. Expert validation results indicated that the e-module was highly valid, with scores of 86.43% from subject matter experts, 91.56% from media experts, and 95.63% from instructional design experts. Practicality testing showed positive responses from teachers (92.14%) and students (82.24%), indicating that the e-module was practical and easy to implement in classroom learning. The effectiveness evaluation revealed a significant improvement in students’ statistical literacy. The average score increased from 58.00 on the pretest to 82.06 on the posttest. Furthermore, the N-Gain value reached 0.59, indicating a moderate improvement category, while Cohen’s effect size of 0.93 demonstrated a large practical effect. Classical learning mastery reached 81.25%, and the independent-samples t-test showed a significant difference between the experimental and control groups (p = 0.000 < 0.05). These findings demonstrate that the STEM-based interactive e-module is valid, practical, and effective for enhancing students’ statistical literacy and supporting meaningful mathematics learning in the digital era.